2021
DOI: 10.1016/j.jvscit.2020.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid emergency room management of a ruptured abdominal aortic aneurysm

Abstract: Patients with a ruptured abdominal aortic aneurysm (rAAA) still have high mortality. Rapid diagnosis and treatment are vital for improving survival outcomes. rAAA management has evolved regarding these factors. We have reported the case of a 70-year-old man with an rAAA that was rapidly diagnosed and treated in a hybrid emergency room (ER). A hybrid ER is an integrated ER capable of computed tomography scanning, interventional radiology, and surgery in one place. In the present case, the door-to-intervention t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…A cost-effectiveness study regarding the implementation of hybrid rooms was conducted in Japanese hospitals, estimating a benefit of 1.03 quality-adjusted life years (QALYs) with an incremental cost-effectiveness ratio (ICER) of US$35,552 per QALY. The analysis estimated that the implementation of an hybrid room has a probability of 79.3% of being cost-effective 19 , 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A cost-effectiveness study regarding the implementation of hybrid rooms was conducted in Japanese hospitals, estimating a benefit of 1.03 quality-adjusted life years (QALYs) with an incremental cost-effectiveness ratio (ICER) of US$35,552 per QALY. The analysis estimated that the implementation of an hybrid room has a probability of 79.3% of being cost-effective 19 , 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Un estudio desarrollado en hospitales japoneses evaluó la costó-efectividad de una sala hibrida reportando que esta estrategia puede generar una ganancia de 1.03 años de vida ajustado QALY (quality-adjusted life year) y una relación de costo-efectividad incremental ICER (incremental cost-effectiveness ratio) de $35.552 dólares por QALY. Se estimo que la implementación de la sala hibrida tendría una probabilidad de ser costo-efectivo del 79.3% 19 , 20 .…”
Section: Discussionunclassified
“…Kinoshita et al was the first to report on the effectiveness of the installation of a hybrid ER in the trauma resuscitation on clinical outcomes and prognosis achieved the innovative trauma workflow. 10 In their historical controlled study, time to initiation of CT (Conventional group 26 [21][22][23][24][25][26][27][28][29][30][31][32] vs. hybrid ER 11 [8][9][10][11][12][13][14][15][16] min; p < 0.0001) and an emergency procedure (68 [51-85] vs. 47 [37-57] min; p < 0.0001) were both shorter in the hybrid ER group. A significant association was found between the hybrid ER and decreased mortality (adjusted odds ratio [aOR], 0.50; 95% confidence interval [CI], 0.29-0.85; p = 0.011) and reduced deaths from exsanguination (aOR, 0.17; 95% CI, 0.06-0.47; p = 0.001).…”
Section: Clinical Experience With Severe Trauma In the Hybrid Ermentioning
confidence: 98%
“…A significant association was found between the hybrid ER and decreased mortality (adjusted odds ratio [aOR], 0.50; 95% confidence interval [CI], 0.29-0.85; p = 0.011) and reduced deaths from exsanguination (aOR, 0.17; 95% CI, 0.06-0.47; p = 0.001). The times to initiation of CT and emergency bleeding control procedures were also both shorter in the hybrid ER group versus the Conventional group (11 [8-16] vs. 26 [21][22][23][24][25][26][27][28][29][30][31][32] The first retrospective observational study on blood transfusion amounts during resuscitation in the hybrid ER was reported by Watanabe et al The amount of blood transfused was significantly lower in the hybrid ER versus nonhybrid ER group (whole blood: 8 vs. 14 units, p = 0.004; red blood cells: 2 vs. 6 units, p = 0.012; fresh frozen plasma: 6 vs. 9 units, p = 0.021). 29 This difference remained after propensity score matching (whole blood: 6 [4-16.5] vs. 28 units, p = 0.015; red blood cells: 2 [0-8.5] vs. 8 [2.75-26.5] units, p = 0.020; fresh frozen plasma: 6 [3.5-7.5] vs. 18 [5.5-27] units, p = 0.057).…”
Section: Clinical Experience With Severe Trauma In the Hybrid Ermentioning
confidence: 99%
See 1 more Smart Citation